The effect of organic fertilizers on the spelt yield and the yield of its components - Pospišil, Ana (Array, 2021)
The aim of this study was to determine the effect of fertilization with organic fertilizers Fertil Supernova and Ilsamin N90 on the yield and yield components of three spelt varieties. The study was conducted on an anthropogenized eutric cambisol at the experimental site of the Faculty of Agriculture in Zagreb during 2015/16, 2016/17, and 2017/18, respectively. The study included three varieties of spelt, Nirvana, Ostro, and Bc Vigor, as well as a topdressing with organic fertilizers and a control (without topdressing). The first topdressing at the beginning of spring vegetation consisted of the application of organic fertilizer Fertil Supernova in the amount of 300 kg ha-1, while the second topdressing at the end of tillering consisted of a foliar application of Ilsamin N90 in the amount of 3 l ha-1. The spelt yield and its yield components were significantly influenced by weather conditions, primarily by the amount and distribution of precipitation. The studied spelt varieties did not significantly differ in the grain yield. In all three research years, the variety Nirvana has achieved the significantly largest number of ears per m2. Topdressing with organic fertilizers had a positive impact on the yield of the hulled spelt grain only in the dry year of 2016/17. Topdressing with organic fertilizers did not have a significant impact on the yield components.